Detail of local flora and fauna - Ghosh, Ayan (2023)
Detail of a monkey plucking mangoes. Stevens was keen to provide an Indian context to his buildings, not only through architectural forms but also by the depiction of Indian flora and fauna, and how they behave in their natural environment. Stevens himself designed the artwork of various flora and fauna scenes that find extensive depiction in the BMC building.